In vitro and in vivo drug screens of tumor cells identify novel therapies for high‐risk child cancer - Loretta M S Lau; Chelsea Mayoh; Jinhan Xie; Paulette Barahona; Karen L MacKenzie; Marie Wong; Alvin Kamili; Maria Tsoli; Tim W Failes; Amit Kumar; Emily V A Mould; Andrew Gifford; et al. (EMBO Molecular Medicine)
Abstract Biomarkers which better match anticancer drugs with cancer driver genes hold the promise of improved clinical responses and cure rates. We developed a precision medicine platform of rapid high‐throughput drug screening (HTS) and patient‐derived xenografting (PDX) of primary tumor tissue, and evaluated its potential for treatment identification among 56 consecutively enrolled high‐risk pediatric cancer patients, compared with conventional molecular genomics and transcriptomics. Drug hits were seen in the majority of HTS and PDX screens, which identified therapeutic options for 10 patients for whom no targetable molecular lesions could be found. Screens also provided orthogonal proof of drug efficacy suggested by molecular analyses and negative results for some molecular findings. We identified treatment options across the whole testing platform for 70% of patients. Only molecular therapeutic recommendations were provided to treating oncologists and led to a change in therapy in 53% of patients, of whom 29% had clinical benefit. These data indicate that in vitro and in vivo drug screening of tumor cells could increase therapeutic options and improve clinical outcomes for high‐risk pediatric cancer patients.